(untitled) (Research, Society and Development, 2021)
The Northeast is a region that stands out as the main fruit producer in Brazil, with a great diversity of tropical fruits still little explored, such as umbu that has significant amounts of nutrients, in this context, this study aimed to develop a tropical juice of umbu from frozen pulp and fruit in-natura. All samples were submitted to microbiological analysis for 90 days, physical-chemical analysis and the determination of bioactive compounds during 120 days of storage. The results found in both juices, presented good microbiological, physicochemical and nutritional characteristics, during the studied storage period. Therefore, umbu juices were obtained with adequate technological parameters and high potential for valorization of this regional fruit, with characteristics to meet the growing demand for nutritious food and with practicality for consumption.